2018
DOI: 10.1080/1828051x.2018.1429955
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary supplementation of natural and fermented herbs on growth performance, nutrient digestibility, blood parameters, meat quality and fatty acid composition in growing-finishing pigs

Abstract: The present experiment was conducted to determine effects of herbs (Artemisia capillaris and Acanthopanax senticosus) in natural and fermented forms on growth performance, nutrient digestibility, blood parameters, meat quality and fatty acid composition in growing-finishing pigs. A total of 96 pigs [(Landrace  Yorkshire)  Duroc] with an average initial body weight (BW) of 25.46 ± 1.07 kg were randomly allotted into one of three dietary treatments. The dietary treatments included: (1) CON (basal diet), (2) NH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 61 publications
(83 reference statements)
2
17
0
1
Order By: Relevance
“…Similar to the positive effects on growth performance that we observed, a previous study showed that daily feeding with the fermented herbal blend for 6 weeks improved the growth performance of broilers ( Hinz et al., 2019 ). Lei et al., (2018) also reported the promotion effect of 16 weeks feed fermented herbs supplementation on production performance of growing-finishing pigs.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Similar to the positive effects on growth performance that we observed, a previous study showed that daily feeding with the fermented herbal blend for 6 weeks improved the growth performance of broilers ( Hinz et al., 2019 ). Lei et al., (2018) also reported the promotion effect of 16 weeks feed fermented herbs supplementation on production performance of growing-finishing pigs.…”
Section: Discussionmentioning
confidence: 98%
“…), inhibited the growth of Escherichia coli and enhanced the humoral immune functioning ( Xie et al., 2016 ). In past studies, PF have often been used in the aquaculture and livestock industries in the form of feed supplements to improve the production performance, but there are few reports their use in the treatment of avian diseases ( Wang et al., 2017 ; Lei et al.,2018 ; Abarike et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…We speculate that some original compounds in A. annua may affect albumen synthesis, and these compounds may be converted into others during fermentation. It was earlier reported that fermented herbs (Artemisia capillaris and Acanthopanax senticosus) increased polyunsaturated fatty acid content in the Longissimus dorsi muscle of pigs compared with non-fermented herbs (Lei et al, 2018). The brown coloration of the eggshell is considered as an important eggshell quality parameter and has a positive impact on consumer preference (Samiullah et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the treatment groups showed no variations in the sensory attributes (color, tenderness, flavor, palatability and juiciness), suggesting that there was no negative impact on the meat consumed. Similarly, Lei et al [32] reported that fermented herbs exert no effect on the sensory attributes and meat color. Moreover, eating quality parameters by which consumers judge the meat quality are highly subjective, variable and invisible [33].…”
Section: Discussionmentioning
confidence: 99%